Anatomic association between the gastrocolic trunk of Henle and right colic artery by high-quality CT venography - Xinzhe Zhao; Hongda Zhang; Hengyu Zhao; Decan Kong; Weijie Zeng; Feng Gao; Xiaochun Meng; Jia Ke (Scientific Reports)
Abstract In hepatic flexure and transverse colon cancer surgeries, mobilizing the right mesocolon and precisely dissecting the gastrocolic trunk of Henle (GTH) are crucial. Previous classifications of GTH tributaries do not guide radical right hemicolectomy due to post-procedural anatomical acquisition. This study analyzed vessel associations, including the middle colic vein (MCV) converging site, right colic artery (RCA) presence, and other GTH tributaries, using ultra-thin CT for reconstruction. GTH anatomy was categorized into medial and lateral types based on colic tributary convergence relative to ASPDV. Results showed the colic tributary joined GTH lateral to ASPDV in 45.81% and medial in 54.19% of cases. RCA presence was strongly linked to the lateral GTH type (56.76% vs. 43.24%, p < 0.001) when RCA was absent. MCV converged into the superior mesenteric vein (SMV) on the left side in 23.15% of cases, correlating with the right colic vein presence (odds ratio = 3.563, p = 0.007). This novel GTH variation pattern via high-level CT venography significantly correlates with RCA presence, aiding surgeons in anticipating GTH anatomy during laparoscopic radical right hemicolectomy.